2011
DOI: 10.1002/app.34250
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of zwitterionic sulfobetaine group functional polyurethanes via “click” reaction

Abstract: Deletion of chromosome 22q11.2 is considered one of the most frequent genetic causes of cardiovascular malformations. It is frequently associated with conotruncal malformations, but may also be present among patients with nonconotruncal malformations. The aim of the present study was to establish the prevalence of the 22q11.2 deletion in an unselected population‐based cohort of children with various cardiovascular malformations. The study population was defined as children born in 2000–2008 who were registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The problem of incomplete conversion unbalancing the charge neutrality of polyzwitterions in post-polymerization modifications can in principle be avoided when reacting the precursor polymer with prefabricated zwitterionic reagents ( Figure 11) [193,[411][412][413][414][415][416][417][418]. Still, this implies the judicious choice of the reactive groups used for the modification.…”
Section: P-51mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of incomplete conversion unbalancing the charge neutrality of polyzwitterions in post-polymerization modifications can in principle be avoided when reacting the precursor polymer with prefabricated zwitterionic reagents ( Figure 11) [193,[411][412][413][414][415][416][417][418]. Still, this implies the judicious choice of the reactive groups used for the modification.…”
Section: P-51mentioning
confidence: 99%
“…If one of these functional groups is fixed on the precursor polymer and the other one to the zwitterionic reagent, this coupling strategy holds both the potential for high coupling efficiencies and selectivities as well as (for charge neutrality) harmless residual reactive sites if remaining. So far, the use of zwitterionic alkynes has been preferred, which are coupled to polymeric azides ( Figure 12) [193,[414][415][416][417][418]. Still, the inverse strategy should be equally feasible.…”
Section: P-52mentioning
confidence: 99%
“…For example, Zhao and coworkers grafted zwitterionic polymer of poly(sulfobetainemethacrylate) (PSBMA) on PSU membrane via surface‐initiated atom transfer radical polymerization and demonstrated enhanced protein antifouling properties and good blood compatibility. Our previous studies also showed polyurethane membrane grafted with SB materials enhance their biocompatibility . It can be expected, therefore, that the surface functionalization of hydrophobic PSU with zwitterionic SB is highly desirable to develop superior antifouling PSU materials and may have potential applications in biomedical field.…”
Section: Introductionmentioning
confidence: 88%
“…As part of our continuous interest in developing synthetic methods for the preparation and modification of various polymer materials, we report herein modification of PSU by this modular approach to yield zwitterionic structure as shown in Scheme . The chemical structures changes of functionalized PSU membrane were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfobetaine (SB) is a zwitterionic molecule containing both cationic and anionic groups, and its polymer has demonstrated better antifouling performance and stability over PEG [19][20][21][22]. Our previous studies also showed that polyurethane [23,24], polysulfone [13], and PVA-co-PE nanofiber [25] membrane grafted with SB materials enhanced their biocompatibility. To the best of our knowledge, there are no reports on fabricating zwitterionic sulfobetaine functional polysulfone membrane via the combination of the ATRP and "click" chemistry.…”
Section: Introductionmentioning
confidence: 97%